Espectroscopia Raman dos aminoácidos L-metionina e DL-alanina e de nanotubos de carbono - Lima Júnior, José Alves de (2008)
This work describes polarized Raman scattering measurements in L-methionine and in DL-alanine (two amino acids) crystals and in several samples of single-walled carbon nanotubes (SWNT). In L-methionine crystal the Raman spectra were obtained from 17 K to 295 K in the spectral range from 50 cm-1 to 3100 cm-1, but no indication of a phase transition was observed. At room temperature, Raman scattering measurements were also performed for pressure up to 5 GPa. Several changes observed in the spectra were interpreted as due to structural phase transition undergone by L-methionine crystal at ~ 2.1 GPa. The results for decompression show that the phase transition is reversible with a hysteresis of ~ 0.8 GPa. In DL-alanine crystal the Raman spectra were obtained at temperatures from 15 K to 295 K over the spectral range 50 cm-1 - 3100 cm-1. No evidence of structural phase transition was found in this range of temperature, although information about diverse modes of the crystal were furnished. Samples of SWNT’s studied were prepared with metallic catalysts using the arc voltaic method. MnNiCo was the main compound of the first series and FeNiCo, the main compound of the second. In both sets it was observed that Cerium (Ce) insertion induces in the sub-set, probed with the 2.41 eV excitation energy, a narrowing of the diameter distribution favoring the tubes with smaller diameter. The Raman scattering measurements in a commercial sample of SWNT’s show a discontinuity at about 2 GPa. The discontinuity was represented by a changing in the slope of the frequency versus pressure for tangential modes. The measurement was performed twice, using two different solutions of surfactants, sodium dodecil sulfate (SDS) and plurocic acid F127 (F127), and the results were similar. The anomaly was interpreted as due to the deformation of the tubes as predicted theoretically. Two sets of three samples of SWNT’s containing different levels of lithium insertion were also analyzed by Raman spectroscopy. Each set of sample was formed by a sample with lithium, a sample without lithium and a sample with partial insertion of lithium. The results show that the lithium is efficiently intercalated with both lithium containing compound (LiCO3/NiO/CoO and LiNi0.5Co0.5O2), but the mechanism of intercalation differs from one to the other. The intercalation is unstable when lithium is intercalated interstitially (LiNi0.5Co0.5O2) and it can be removed almost completely by washing the sample, but if the lithium is intercalated inside the tubes (LiCO3/NiO/CoO) it can not be removed by the same process.